Relationship between autophagy, apoptosis and endoplasmic reticulum stress induced by melatonin in osteoblasts by septin7 expression - Cui, Cui (Mol Med Rep, 2020)
Melatonin secreted by the pineal body is associated with the occurrence and development of idiopathic scoliosis. Melatonin has a concentration-dependent dual effect on osteoblast proliferation, in which higher concentrations can inhibit osteoblast proliferation and induce apoptosis; however, the underlying mechanism remains unclear. In the present study, flow cytometry was used to demonstrate that osteoblast cells treated with melatonin exhibited significantly increased early and late stage apoptotic rates as the concentration increased. Chromatin condensation in the nucleus and apoptotic body formation could be observed using fluorescent microscopy in osteoblast cells treated with 2 mM melatonin. Western blotting results showed that there was an upregulation in the expression of apoptosis marker proteins [poly (ADP-ribose) polymerase 1 (PARP-1)], endoplasmic reticulum stress [ERS; C/EBP homologous protein (CHOP) and glucose-regulated protein, 78 kDa (GRP78)] and autophagy [microtubule-associated protein 1 light chain 3β (LC3)-I/LC3II]. PARP-1 expression was not altered when treated with ERS inhibitor 4PBA and autophagy inhibitor 3MA, whereas 4PBA or 3MA in combination with 2 mM melatonin (or the three together) significantly increased PARP-1 expression. Furthermore, the use of septin7 small interfering RNA confirmed that increased expression of GRP78 and CHOP was related to septin7, and melatonin- mediated ERS was necessary for septin7 activation. These findings suggest that ERS and autophagy might occur in the early stage of treatment with a high concentration of melatonin, and each might play a protective role in promoting survival; in a later stage, ERS and autophagy might interact and contribute to the induction of apoptosis. Overall, the results indicated that septin7 may be a target protein of melatonin-induced ERS.